Curable composition, alkali develop ability resist and cured object

JP2025023381APending Publication Date: 2025-02-17KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023127448
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、冷熱衝撃試験における信頼性を改善させた硬化性組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023381000001
    Figure 2025023381000001
  • Figure 2025023381000002
    Figure 2025023381000002
  • Figure 2025023381000003
    Figure 2025023381000003
Patent Text Reader

Abstract

To provide a curable composition capable of improving reliability in cold-heat shock test when being used in production of a substrate laminate.SOLUTION: There is provided a curable composition which is a hydrosilylation reaction object of compounds of following (α) to (δ), and includes, a modified poly cyclic organosiloxane compound in which, when a substance amount of (α) is α mole, and a substance amount of (β) is β mole, 0.25≤β / α≤1.5 is satisfied: (α) a cyclic siloxane compound having at least two SiH groups in one molecule; (β) a straight chain siloxane compound having on both terminals thereof, SiH groups; (γ) at least one kind selected from a diallyl isocyanurate and / or alkenyl compound having a phenolic hydroxyl group; (δ) an alkenyl compound having in one molecule, a polymerizable functional group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alkali developable resist capable of providing a pattern by alkali development, a cured product, and a curable composition. [Background technology]

[0002] Image sensors such as CMOS sensors and CCD sensors are used in digital cameras, smartphones, etc. In recent years, the use of these sensors has increased with the spread of surveillance cameras in automobiles and factories, and there has been an increasing demand for smaller size and higher resolution.

[0003] The substrate laminate constituting the image sensor has a hollow structure in which, for example, a semiconductor element substrate having a light receiving element and a glass substrate are bonded together with an adhesive. The substrate laminate having a hollow structure can be obtained, for example, by applying a liquid adhesive such as an epoxy resin or an acrylic resin to the periphery of the semiconductor element substrate, placing a glass substrate to be a sealing substrate, and then heating the substrate to harden the liquid adhesive. In addition, a method of using a photosensitive composition instead of the liquid adhesive for the purpose of improving the pattern accuracy has also been considered.

[0004] For example, Patent Document 1 describes a method for manufacturing a substrate laminate, which includes a step of forming a coating film by applying a photosensitive composition onto a first substrate (e.g., a glass substrate), a step of patterning the obtained coating film, a step of forming a laminate by laminating the first substrate and a second substrate (e.g., a semiconductor device substrate) via the patterned coating film (hereinafter, sometimes referred to as a "pattern film"), and a step of heating the obtained laminate to bond the first substrate and the second substrate. Patent Document 1 also describes that the photosensitive composition contains a cationic polymerizable compound and a photoacid generator (photocationic polymerization initiator), and that in the step of patterning the coating film, the coating film is irradiated with light through a photomask to semi-cure the exposed portion of the coating film, and then developed to form a semi-cure pattern film. Hereinafter, forming a semi-cure pattern film may be referred to as "B-staging". Furthermore, the step of heating a laminate in which a first substrate and a second substrate are laminated with a semi-cured pattern film therebetween to further harden the pattern film and bond the first substrate and the second substrate is sometimes referred to as "C-staging." Note that the "semi-cured state" refers to a state in which there is still room for further hardening of the pattern film in the step of heating the laminate.

[0005] Substrate laminates used in image sensors and the like are required to have high durability, and in particular, reliability in thermal shock tests (such as cracking and peeling of the cured product). However, the technology described in Patent Document 1 leaves room for improvement in the reliability of manufactured substrate laminates in thermal shock tests. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-62048 A Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above, an object of the present invention is to provide a curable composition which, when used in the production of a substrate laminate, has improved reliability in a thermal shock test. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above-mentioned problems and have completed the present invention.

[0009] That is, the present invention has the following configuration. 1) A curable composition comprising a modified polycyclic organosiloxane compound which is a hydrosilylation reaction product of the following compounds (α) to (δ), and in which, when the amount of the substance (α) is α moles and the amount of the substance (β) is β moles, the relationship 0.25≦β / α≦1.5 is satisfied: (α) a cyclic siloxane compound having at least two SiH groups per molecule, (β) a linear siloxane compound having SiH groups at both ends, (γ) at least one selected from the group consisting of an alkenyl compound having a structure represented by the following formula (X1) and / or an alkenyl compound having a phenolic hydroxyl group, (δ) An alkenyl compound having a polymerizable functional group in one molecule.

[0010] [ka] 2) The curable composition according to 1), which has at least two polymerizable functional groups.

[0011] 3) The curable composition according to either 1) or 2), wherein the linear siloxane compound used in the reaction is 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane.

[0012] 4) The curable composition according to any one of 1) to 3), which is further a reaction product with an alkenyl compound having an alcoholic hydroxyl group.

[0013] 5) The curable composition according to any one of 1) to 4), wherein the modified polycyclic organosiloxane compound has a SiH value of 1.20 mmol / g or less.

[0014] 6) The curable composition according to any one of 1) to 5), which contains a compound having two or more (meth)acryloyl groups.

[0015] 7) The curable composition according to any one of 1) to 6), which contains a polymerization initiator.

[0016] 8). An alkali developable resist using the curable composition according to any one of 1) to 7).

[0017] 9) A cured product obtained by curing the curable composition according to any one of 1) to 7). Effect of the Invention

[0018] According to the present invention, it is possible to provide a curable composition having improved reliability in thermal shock tests. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Preferred embodiments of the present invention will be described in detail below, but the present invention is not limited thereto. In addition, all academic and patent documents described in this specification are incorporated herein by reference.

[0020] First, the terms used in this specification are explained. "Photopolymerization initiator" refers to a compound that generates cations or radicals as active species upon irradiation with light. The term "active species" includes radicals, cations, and anions. "Polymerizable functional group" refers to a functional group that polymerizes in a chain manner. "Alkali-soluble group" refers to a functional group that increases the solubility in an alkaline solution by interacting with or reacting with an alkali. "Polysiloxane structure" refers to a structure in which siloxane units (Si-O-Si) are linked. "Solid content" refers to the non-volatile components in the composition, and "total solid content" refers to the total amount of the components of the composition excluding the solvent.

[0021] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. When the compound name is followed by "based" to represent the name of a polymer, it means that the repeating unit of the polymer is derived from the compound or its derivative. Acrylates and methacrylates may be collectively referred to as "(meth)acrylates". Acryloyl groups and methacryloyl groups may be collectively referred to as "(meth)acryloyl groups".

[0022] Unless otherwise specified, the components and functional groups exemplified in this specification may be used alone or in combination of two or more kinds.

[0023] <Curable composition> The curable composition according to the present invention is a hydrosilylation reaction product of the following compounds (α) to (δ), and is characterized in that it contains a modified polycyclic organosiloxane compound in which, when the amount of substance (α) is α moles and the amount of substance (β) is β moles, 0.25≦β / α≦1.5. (α) a cyclic siloxane compound having at least two SiH groups per molecule, (β) a linear siloxane compound having SiH groups at both ends, (γ) at least one selected from the group consisting of an alkenyl compound having a structure represented by the following formula (X1) and / or an alkenyl compound having a phenolic hydroxyl group, (δ) An alkenyl compound having a polymerizable functional group in one molecule.

[0024] [ka] In other words, the curable composition according to the present invention is a curable compound containing a modified polycyclic organosiloxane compound (hereinafter sometimes referred to as "component (A)") having at least one member selected from the group consisting of a structure represented by the following formula (X2) and a phenolic hydroxyl group in the molecule, a linear siloxane structure, and a polymerizable functional group. From the viewpoint of curability, it is particularly preferable that the compound has at least two polymerizable functional groups. The straight lines extending from the two nitrogen atoms in the structure represented by the following formula (X2) do not represent methyl groups, but indicate that the nitrogen atoms are bonded to other groups (sites).

[0025] [ka]

[0026] The curable composition of the present invention can be dissolved in an alkaline aqueous solution by having the structure represented by the above formula (X2) or a hydroxyl group in the same molecule, and can be used as a resist material that can be developed in an alkaline solution.

[0027] The modified polycyclic organosiloxane compound (component (A)) used in the curable composition of the present invention is a polymer containing a linear siloxane structure and a polycyclic siloxane structure in the main chain. The "polycyclic siloxane structure" means a cyclic molecular structure skeleton having siloxane units (Si-O-Si) as ring components.

[0028] Component (A) has a SiH value of 1.20 mmol / g or less, more preferably 0.50 mmol / g or less, and even more preferably 0.15 mmol / g or less.

[0029] Component (A) may be a monocyclic structure or a polycyclic structure. The polycyclic structure may be a polyhedral structure. Among the siloxane units constituting the ring, the T units (XSiO 3 / 2 ) or Q units (SiO 4 / 2 The higher the content of the M unit (XSiO 1 / 2 ) or D unit (X2SiO 2 / 2 The higher the content of X, the more flexible the resulting cured layer tends to be and the more reduced the residual stress tends to be. Here, X represents an organic group.

[0030] The component (A) used in the curable composition of the present invention further has at least two polymerizable functional groups in one molecule. The polymerizable functional group here refers to a functional group that polymerizes or crosslinks when light or heat energy is applied from the outside, and there are no particular limitations on the type of reaction or crosslinking.

[0031] The weight average molecular weight of the component (A) used in the curable compound of the present invention is preferably 10,000 to 50,000, more preferably 20,000 to 40,000, and even more preferably 25,000 to 35,000. When the weight average molecular weight is 10,000 or more, a cured layer having excellent heat resistance tends to be obtained. On the other hand, when the weight average molecular weight is 50,000 or less, the removability of the non-exposed part during development is increased, so that the patterning property tends to be improved.

[0032] Component (A) (modified polycyclic organosiloxane compound: more specifically, a cationically polymerizable compound having a cationically polymerizable functional group, an alkali-soluble group, a linear siloxane structure, and a polycyclic siloxane structure in one molecule) is obtained by a hydrosilylation reaction containing the following compounds (α), (β), (γ), and (δ) as essential components. Compound (α): A polycyclic siloxane compound having at least two SiH groups (hydrosilyl groups) in one molecule. Compound (β): A linear siloxane compound having SiH groups (hydrosilyl groups) at both ends Compound (γ): A compound having a carbon-carbon double bond reactive with a SiH group and an alkali-soluble group in one molecule (an alkenyl compound having a structure represented by (X1) and / or an alkenyl compound having a phenolic hydroxyl group) Compound (δ): A compound having a carbon-carbon double bond reactive with a SiH group and a cationic polymerizable functional group in one molecule (an alkenyl compound having a polymerizable functional group in one molecule).

[0033] [ka] (Compound (α)) The compound (α) is a polycyclic siloxane compound having at least two SiH groups in one molecule, and for example, a cyclic compound having at least two SiH groups in one molecule described in International Publication No. 96 / 15194 can be used. The polycyclic siloxane may have a polycyclic structure, and the polycyclic structure may be a polyhedral structure. In order to form a cured layer having high heat resistance and mechanical strength, the compound (α) is preferably a polycyclic siloxane having three or more SiH groups in one molecule. From the viewpoint of heat resistance and light resistance, the group present on the Si atom is preferably either a hydrogen atom or a methyl group.

[0034] The cyclic polysiloxane is represented, for example, by the following general formula (1).

[0035] [ka]

[0036] In general formula (1), R 1 , R 2 and R 3each independently represents a monovalent organic group having 1 to 20 carbon atoms, m represents an integer of 2 to 10, and n represents an integer of 0 to 10. In order to easily carry out the hydrosilylation reaction, it is preferable that m is 3 or more. In order to easily carry out the hydrosilylation reaction, it is preferable that m+n is 3 or more and 12 or less. In order to more easily carry out the hydrosilylation reaction, it is preferable that n is 0.

[0037] R 1 , R 2 and R 3 R is preferably an organic group composed of an element selected from the group consisting of C, H, and O. 1 , R 2 and R 3 Examples of R include alkyl groups, hydroxyalkyl groups, alkoxyalkyl groups, oxyalkyl groups, and aryl groups. Among these, chain alkyl groups such as methyl groups, ethyl groups, propyl groups, hexyl groups, octyl groups, decyl groups, and dodecyl groups, cyclic alkyl groups such as cyclohexyl groups and norbornyl groups, and phenyl groups are preferred. From the viewpoint of availability of cyclic polysiloxanes, R 1 , R 2 and R 3 R is preferably a chain alkyl group having 1 to 6 carbon atoms or a phenyl group. 1 , R 2 and R 3 As the alkyl group, a chain alkyl group having 1 to 6 carbon atoms is preferable, and a methyl group is more preferable.

[0038] Examples of cyclic polysiloxanes represented by general formula (1) include 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane, 1-propyl-3,5,7-trihydrogen-1,3,5,7-tetramethylcyclotetrasiloxane, 1,5-dihydrogen-3,7-dihexyl-1,3,5,7-tetramethylcyclotetrasiloxane, 1,3,5-trihydrogen-1,3,5-trimethylcyclotrisiloxane, 1,3,5,7,9-pentahydrogen-1,3,5,7,9-pentamethylcyclopentasiloxane, and 1,3,5,7,9,11-hexahydrogen-1,3,5,7,9,11-hexamethylcyclohexasiloxane. Among these, from the viewpoints of availability and reactivity of the SiH group, 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane (in the general formula (1), m=4, n=0, and R 1 is a methyl group).

[0039] Compound (α) can be obtained by a known synthesis method. For example, the cyclic polysiloxane represented by general formula (1) can be synthesized by the method described in International Publication No. 96 / 15194. The cyclic polysiloxane having a polyhedral skeleton can be synthesized by the method described in Japanese Patent Application Laid-Open No. 2004-359933, Japanese Patent Application Laid-Open No. 2004-143449, Japanese Patent Application Laid-Open No. 2006-269402, etc. In addition, a commercially available polycyclic siloxane compound may be used as compound (α).

[0040] (Compound (β)) As linear siloxane compounds having SiH groups (hydrosilyl groups) at both ends, there are polysiloxanes whose ends are blocked with dimethylhydrogensilyl groups, and dimethylhydrogensiloxane units (H(CH3)2SiO 1 / 2 units), and SiO2 units, SiO 3 / 2 Examples of the compound (β) include polysiloxanes having one or more siloxane units selected from the group consisting of SiO units and SiO. The compound (β) preferably has two SiH groups.

[0041] Specific examples of compound (β) include 1,1,3,3-tetramethyldisiloxane, 1,3-diethyl-1,3-dimethyldisiloxane, 1,3-dimethyl-1,3-diphenyldisiloxane, 1,1,3,3,5,5-hexamethyltrisiloxane, 3-ethyl-1,1,3,5,5-pentamethyltrisiloxane, and 3,3-diethyl-1,1,5,5-tetramethyltrisiloxane. Examples of suitable siloxanes include 1,1,3,5,5-pentamethyl-3-phenyltrisiloxane, 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane, 1,1,1,3,5,7,7,7-octamethyltetrasiloxane, 1,1,3,3,5,5,7,7-octamethyltetrasiloxane, 1,1,3,3,5,5,7,7,9,9-decamethylpentasiloxane, etc. Among these, 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane is more preferred from the viewpoint of improving the toughness of the resin.

[0042] (Compound (γ)) Compound (γ) is a compound having a carbon-carbon double bond reactive with a SiH group and an alkali-soluble group in one molecule. The alkali-soluble group in compound (γ) is the same as the alkali-soluble group in the curable composition described above, and the preferred embodiments are also the same. That is, compound (γ) preferably has one or more alkali-soluble groups selected from the group consisting of X2 groups and phenolic hydroxyl groups, and more preferably has X2 groups.

[0043] Compound (γ) has a group (alkenyl group) containing a carbon-carbon double bond reactive with a SiH group. Examples of the alkenyl group contained in compound (γ) include the same alkenyl groups as those exemplified as the alkenyl group contained in compound (γ), and the preferred embodiments are also the same. That is, compound (γ) preferably has, as the alkenyl group, one or more selected from the group consisting of a vinyl group and an allyl group. The number of alkenyl groups preferably contained in compound (γ) is two.

[0044] Specific examples of the compound (γ) include diallyl isocyanurate and 2,2′-diallyl bisphenol A. In order to more stably maintain the semi-cured state of the pattern film, diallyl isocyanurate is preferred.

[0045] (Compound (δ)) Compound (δ) is a compound having a carbon-carbon double bond reactive with a SiH group (hydrosilyl group) and a polymerizable functional group in one molecule. Compound (γ) preferably has a cationic polymerizable group or a radical polymerizable group as the polymerizable functional group. In particular, compound (γ) preferably has a cationic polymerizable group as the polymerizable functional group, and among the cationic polymerizable groups, it is preferable to have an epoxy group, more preferably have one or more selected from the group consisting of an alicyclic epoxy group and a glycidyl group, and further preferably have an alicyclic epoxy group.

[0046] Examples of groups containing a carbon-carbon double bond reactive with SiH groups (hereinafter, sometimes simply referred to as "alkenyl groups") include vinyl groups, allyl groups, methallyl groups, 2-allylphenyl groups, 3-allylphenyl groups, 4-allylphenyl groups, 2-(allyloxy)phenyl groups, 3-(allyloxy)phenyl groups, 4-(allyloxy)phenyl groups, 2-(allyloxy)ethyl groups, 2,2-bis(allyloxymethyl)butyl groups, 3-allyloxy-2,2-bis(allyloxymethyl)propyl groups, vinyl ether groups, etc. From the viewpoint of reactivity with SiH groups, it is preferable that the compound (δ) has at least one alkenyl group selected from the group consisting of vinyl groups and allyl groups.

[0047] Specific examples of the compound (δ) include 1-vinyl-3,4-epoxycyclohexane, allyl glycidyl ether, diallyl monoglycidyl isocyanurate, monoallyl diglycidyl isocyanurate, etc. From the viewpoint of reactivity in cationic polymerization, the compound (δ) is preferably a compound having an alicyclic epoxy group, and particularly preferably 1-vinyl-3,4-epoxycyclohexane.

[0048] (Other starting materials) In the hydrosilylation reaction, in addition to the above-mentioned compound (α), compound (β), compound (γ), and compound (δ), other starting materials may be used. For example, as the other starting materials, alkenyl-containing compounds different from the above-mentioned compound (γ) and compound (δ) (hereinafter, sometimes referred to as "other alkenyl-containing compounds") may be used.

[0049] In order to increase the affinity with the alkaline developer and improve the development speed, the component (A) may be synthesized using an alkenyl compound (π) having an alcoholic hydroxyl group. Preferred examples of the alkenyl compound (π) having an alcoholic hydroxyl group include allyl alcohol, 3-buten-1-ol, 4-penten-1-ol, 5-hexen-2-ol, ethylene glycol monoallyl ether, and 3-allyloxy-1,2-propanediol, and ethylene glycol monoallyl ether is preferred in terms of development speed.

[0050] In order to obtain a cured layer having excellent heat resistance, it is preferable to use a compound having two or more alkenyl groups in one molecule (hereinafter, sometimes referred to as "compound (ε)") as the other alkenyl group-containing compound. If compound (ε) is used, the number of crosslinking points increases during the hydrosilylation reaction, and the heat resistance of the obtained cured material tends to be improved.

[0051] Specific examples of the compound (ε) include diallyl phthalate, triallyl trimellitate, diethylene glycol bisallyl carbonate, 1,1,2,2-tetraallyloxyethane, triallyl cyanurate, triallyl isocyanurate, diallyl monobenzyl isocyanurate, diallyl monomethyl isocyanurate, 1,2,4-trivinylcyclohexane, triethylene glycol divinyl ether, divinylbenzene, divinylbiphenyl, 1,3-diisopropenylbenzene, 1,4-diisopropenylbenzene, 1,3-bis(allyloxy)adamantane, 1,3-bis(vinyloxy)adamantane, 1,3,5-tris(allyloxy)adamantane, 1,3,5-tris(vinyloxy)adamantane, dicyclopentadiene, vinylcyclohexene, 1,5-hexadiene, 1,9-decadiene, diallyl ether, and oligomers thereof.

[0052] In order to further improve the heat resistance of the resulting cured layer, the compound (ε) is preferably diallyl monomethyl isocyanurate.

[0053] In order to further suppress the film loss during development, it is preferable to use a compound having an alkenyl group and a (meth)acryloyl group in one molecule (hereinafter, sometimes referred to as "compound (ζ)") as another alkenyl group-containing compound. When compound (ζ) is used, a (meth)acryloyl group is introduced into the compound, so that the number of reaction points for the radical polymerization reaction becomes relatively large. This makes it possible to increase the alkali resistance of the semi-cured exposed area.

[0054] Specific examples of the compound (ζ) include vinyl acrylate, vinyl methacrylate, allyl acrylate, allyl methacrylate, 2-butenyl acrylate, 2-butenyl methacrylate, etc. In order to further suppress the film loss during development, the compound (ζ) is preferably one or more selected from the group consisting of vinyl acrylate and allyl acrylate, and more preferably allyl acrylate.

[0055] (Hydrosilylation reaction) The order and method of hydrosilylation reaction for obtaining modified polycyclic organosiloxane compounds are not particularly limited.For example, the modified polycyclic siloxane compounds can be obtained by hydrosilylation reaction according to the method described in International Publication No. 2009 / 075233 using the above-mentioned compound (α), compound (β), compound (γ), compound (δ), and other starting materials that are optional components as needed.The modified polycyclic organosiloxane compounds obtained using the above-mentioned compound (α), compound (β), compound (γ), compound (δ), and other starting materials that are optional components as needed are, for example, polymers that have multiple cationic polymerizable functional groups and multiple alkali-soluble groups in one molecule, and have linear siloxane structures and polycyclic siloxane structures in the main chain.

[0056] Regarding the ratio of each compound in the hydrosilylation reaction, the total substance amount A of alkenyl groups and the total substance amount B of SiH groups among the starting materials preferably satisfy the relationship 1≦B / A≦30, more preferably 1≦B / A≦10, and further preferably 1≦B / A≦1.1.

[0057] In order to stably maintain the semi-cured state of the pattern film while increasing the flexibility of the cured product obtained by B-staging, when the amount of compound (α) in the hydrosilylation reaction is α moles and the amount of compound (β) is β moles, the relationship 0.25≦β / α≦1.5 must be satisfied, and preferably 0.25≦β / α≦1.4.

[0058] In order to obtain a photosensitive composition having excellent patterning properties, the charge ratio of compound (γ) to compounds (α) and (β) in the hydrosilylation reaction (mass of compound (γ) / (mass of compound (α)+mass of compound (β))) is preferably 0.1 or more and 0.9 or less, more preferably 0.2 or more and 0.8 or less.

[0059] In order to improve the heat resistance of the cured product obtained by B-staging while stably maintaining the semi-cured state of the pattern film, the charge ratio of compound (δ) to compound (α) in the hydrosilylation reaction (mass of compound (δ) / mass of compound (α)) is preferably 0.1 or more and 1.0 or less, and more preferably 0.2 or more and 0.9 or less.

[0060] When compound (ε) is used as a starting material, in order to obtain a photosensitive composition having excellent patterning properties while improving the heat resistance of the cured product obtained by B-staging, the charge ratio of compound (ε) to compound (α) in the hydrosilylation reaction (mass of compound (ε) / mass of compound (α)) is preferably 0.01 or more and 0.5 or less, and more preferably 0.05 or more and 0.4 or less.

[0061] When compound (ζ) is used as a starting material, in order to ensure the adhesion of the pattern film when it is B-staged while further suppressing film loss during development, the charge ratio of compound (ζ) to compound (α) in the hydrosilylation reaction (mass of compound (ζ) / mass of compound (α)) is preferably 0.1 or more and 0.5 or less, and more preferably 0.2 or more and 0.4 or less.

[0062] For the hydrosilylation reaction, a hydrosilylation catalyst such as chloroplatinic acid, a platinum-olefin complex, or a platinum-vinylsiloxane complex may be used. The hydrosilylation catalyst may be used in combination with a co-catalyst. The amount of the hydrosilylation catalyst (amount of substance) added is not particularly limited, but is preferably 10 to 100% based on the total amount of alkenyl groups contained in the starting material. -8 more than 10 times -1 times or less, more preferably 10 -6 more than 10 times -2 It is less than double.

[0063] The reaction temperature for hydrosilylation may be appropriately set, and is preferably from 30° C. to 200° C., more preferably from 50° C. to 150° C. The oxygen concentration in the gas phase during the hydrosilylation reaction is preferably 3% by volume or less. From the viewpoint of promoting the hydrosilylation reaction, the gas phase may contain 0.1% by volume to 3% by volume of oxygen.

[0064] A solvent may be used in the hydrosilylation reaction. As the solvent, one type of solvent alone or a mixed solvent of two or more types of solvents may be used. Examples of the solvent include hydrocarbon solvents such as benzene, toluene, xylene, hexane, and heptane; ether solvents such as tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and diethyl ether; ketone solvents such as acetone and methyl ethyl ketone; and halogen solvents such as chloroform, methylene chloride, and 1,2-dichloroethane. Toluene, xylene, tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and chloroform are preferred because they are easily removed by distillation after the reaction. In the hydrosilylation reaction, a gelation inhibitor may be used as necessary.

[0065] [Compounds containing two or more (meth)acryloyl groups] The compound containing a (meth)acryloyl group (hereinafter, sometimes referred to as "component (B)") is not particularly limited as long as it is a radical polymerizable compound having a (meth)acryloyl group. Examples of the radical polymerizable compound having a (meth)acryloyl group include compounds having at least two acryloyl groups and at least one methacryloyl group in one molecule.

[0066] In order to increase the reactivity of the radical polymerization reaction, thereby increasing the alkali resistance of the semi-cured exposed area, and thereby further suppressing film loss during development, a compound having an acryloyl group is preferred as component (B).

[0067] In order to enhance the alkali resistance of the semi-cured exposed area by increasing the reactivity of the radical polymerization reaction and to further suppress the film loss during development, the component (B) may have two or more (meth)acryloyl groups in one molecule, but a compound having three or more (meth)acryloyl groups in one molecule is preferred from the viewpoint of curability. In order to particularly suppress the film loss during development, a compound containing a (meth)acryloyl group is more preferably a compound having three or more acryloyl groups in one molecule.

[0068] In order to ensure the adhesion of the pattern film during B-staging, the number of (meth)acryloyl groups contained in one molecule of component (B) is preferably 6 or less, more preferably 5 or less, and even more preferably 4 or less. Examples of component (B) having two (meth)acryloyl groups in one molecule include triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate (more specifically, polypropylene glycol #700 diacrylate, etc.), 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, etc.

[0069] Examples of the component (B) having three (meth)acryloyl groups in one molecule include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and glycerin propoxy tri(meth)acrylate.

[0070] Examples of the component (B) having four (meth)acryloyl groups in one molecule include pentaerythritol tetra(meth)acrylate and ditrimethylolpropane tetra(meth)acrylate.

[0071] Component (B) may have a cationic polymerizable functional group. It may also have an alkali-soluble group. However, in order to improve the patterning property and more stably maintain the semi-cured state of the pattern film, it is preferable that the photosensitive composition according to the first embodiment does not contain a compound having a cationic polymerizable functional group and an alkali-soluble group in one molecule as a compound containing a (meth)acryloyl group. In other words, in the curable composition according to the present invention, it is preferable that the compound containing a (meth)acryloyl group is not a compound having a cationic polymerizable functional group and an alkali-soluble group in one molecule.

[0072] [Polymerization initiator] The polymerization initiator (hereinafter sometimes referred to as "component (C)") may be a cationic polymerization initiator and / or a radical polymerization initiator. The cationic polymerization initiator that can be used is not particularly limited, so long as it is an active energy ray cationic polymerization initiator that generates a cationic species or a Lewis acid by active energy rays, or a thermal cationic polymerization initiator that generates a cationic species or a Lewis acid by heat.

[0073] As the thermal cationic polymerization initiator, cationic catalysts such as sulfonium salts, ammonium salts, pyridinium salts, phosphonium salts, iodonium salts, trifluoroacid salts, boron trifluoride ether complex compounds, boron trifluoride, etc., or protonic acid catalysts can be used. They are highly stable until they generate cationic species by heating, so they can be called latent curing catalysts. The polymerization activity changes depending on the type of substituent and the type of anion of the onium salt. In particular, with regard to anions, BF - <AsF6 - <PF6 - <SbF6 - <B(C6F5)4 - It is known that the polymerization activity increases in the order of . In addition, it is known that aluminum complexes and silanol compounds, and aluminum complexes and certain phenolic compounds such as bisphenol S, can act as cationic polymerization catalysts.

[0074] On the other hand, among aromatic onium salts that are also used as active energy ray cationic polymerization initiators, there are some that generate cationic species by heat, and these can also be used as thermal cationic polymerization initiators. Examples include San-Aid SI-60L, SI-80L and SI-100L (Sanshin Chemical Industry Co., Ltd.), RHODORSIL PI2074 (Rhodia Co., Ltd.). Among these cationic polymerization initiators, aromatic onium salts are preferred in that they are easy to handle and have an excellent balance between latency and curability.

[0075] The amount of the cationic polymerization initiator used is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, based on 100 parts by weight of the modified polyorganosiloxane compound (component (A)). If the amount of the cationic polymerization initiator is small, it may take a long time to cure, or a sufficiently cured product may not be obtained. If the amount of the initiator is large, the color of the initiator may remain in the cured product, the product may become colored or bulge due to rapid curing, or the heat and light resistance of the cured product may be impaired, which is undesirable.

[0076] The radical polymerization initiator that can be used is not particularly limited, so long as it is an active energy ray radical polymerization initiator that generates radical species by active energy rays, or a thermal radical polymerization initiator that generates radical species by heat.

[0077] Specific examples of the radical polymerization initiator include acetophenone compounds, acylphosphine oxide compounds, benzoin compounds, benzophenone compounds, α-diketone compounds, biimidazole compounds, polynuclear quinone compounds, triazine compounds, oxime ester compounds, titanocene compounds, xanthone compounds, thioxanthone compounds, ketal compounds, azo compounds, peroxides, 2,3-dialkyldione compounds, disulfide compounds, fluoroamine compounds, etc. In order to further suppress film loss during development, one or more compounds selected from the group consisting of acetophenone compounds, benzophenone compounds, and oxime ester compounds are preferred.

[0078] Examples of acetophenone compounds include 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4'-i-propylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2'-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, 2,2-dimethoxyacetophenone, 2,2-diethoxyacetophenone, 2-methyl-1-(4'-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4'-morpholinophenyl)butan-1-one, and 1-hydroxycyclohexyl phenyl ketone.

[0079] Examples of the acylphosphine oxide compounds include 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.

[0080] Examples of oxime ester compounds include 1,2-octanedione 1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), and the like.

[0081] Examples of the benzoin compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.

[0082] Examples of the benzophenone compounds include benzyl dimethyl ketone, benzophenone, 4,4'-bis(dimethylamino)benzophenone, and 4,4'-bis(diethylamino)benzophenone.

[0083] An example of the α-diketone compound is methyl benzoyl formate.

[0084] Examples of the biimidazole compound include 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5'- Tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2-bromophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4-dibromophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4,6-tribromophenyl)- 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5 2,2'-bis(2-bromophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dibromophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, and 2,2'-bis(2,4,6-tribromophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole.

[0085] Examples of polynuclear quinone compounds include anthraquinone, 2-ethylanthraquinone, 2-t-butylanthraquinone, and 1,4-naphthoquinone.

[0086] Examples of xanthone compounds include xanthone, thioxanthone, and 2-chlorothioxanthone.

[0087] Examples of triazine compounds include 1,3,5-tris(trichloromethyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(2'-chlorophenyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(4'-chlorophenyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(2'-methoxyphenyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(4'-methoxyphenyl)-s-triazine, 2-(2'-furylethylidene)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxystyryl)-s-triazine, 2-(4'-methoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2'-bromo-4'-methylphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2'-thiophenylethylidene)-4,6-bis(trichloromethyl)-s-triazine, and the like.

[0088] In order to further suppress the film loss during development, the amount of the radical polymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, relative to 100 parts by mass of component (B). Also, in order to ensure the adhesiveness of the pattern film during B-staging, the amount of the radical polymerization initiator is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, relative to 100 parts by mass of component (B).

[0089] [solvent] The curable composition according to the present invention may contain a solvent. For example, the photosensitive composition according to the first embodiment can be obtained by dissolving or dispersing the above-mentioned components (A), (B), and (C) and other components described below as necessary in a solvent.

[0090] Specific examples of the solvent include hydrocarbon solvents such as benzene, toluene, hexane, and heptane; ether solvents such as tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and diethyl ether; ester solvents such as ethyl acetate and isobutyl isobutyrate; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; glycol solvents such as propylene glycol 1-monomethyl ether 2-acetate, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, and ethylene glycol diethyl ether; and halogen solvents such as chloroform, methylene chloride, and 1,2-dichloroethane. From the viewpoint of the coatability (film formation stability) of the photosensitive composition, the solvent is preferably an ester solvent, and more preferably isobutyl isobutyrate.

[0091] From the viewpoint of the coatability (film-forming stability) of the photosensitive composition, the amount of the solvent is preferably 10 parts by mass or more and 200 parts by mass or less, and more preferably 20 parts by mass or more and 100 parts by mass or less, per 100 parts by mass of the modified polycyclic organosiloxane.

[0092] [Other ingredients] The curable composition according to the present invention may contain components other than those described above (other components) within the scope of the present invention without impairing the object and effect of the present invention. However, in order to more stably maintain the semi-cured state of the pattern film while further suppressing the film loss during development, the total amount of the above-mentioned components is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more and 100% by mass or less, based on the total solid content of the curable composition. Examples of other components include radical scavengers, colorants, sensitizers, fillers, adhesion improvers, coupling agents such as silane coupling agents, deterioration inhibitors, release agents, flame retardants, flame retardant assistants, surfactants, defoamers, emulsifiers, leveling agents, anti-repellent agents, thixotropy imparting agents, tackifiers, storage stability improvers, light stabilizers, thickeners, plasticizers, reactive diluents, antioxidants, heat stabilizers, electrical conductivity imparting agents, antistatic agents, radiation shielding agents, nucleating agents, lubricants, metal deactivators, and thermal conductivity imparting agents.

[0093] [Resist, cured product, and substrate laminate using the curable composition] Next, a resist using the curable compound of the present invention, a cured product thereof, and a method for producing a substrate laminate using the same will be described.

[0094] The manufacturing method includes a coating film forming step, an exposure step, a development step, a lamination step, and a heating step. In the coating film forming step, a coating film is formed by applying a curable composition onto a first substrate. In the exposure step, the coating film is irradiated with light through a photomask to form an exposed portion made of a semi-cured photosensitive composition and a non-exposed portion in the coating film. In the development step, an alkaline developer is used to remove the non-exposed portion from the substrate to form a patterned coating film on the first substrate. In the lamination step, the first substrate and the second substrate are laminated together via the patterned coating film to form a laminate. In the heating step, the laminate is heated to further harden the semi-cured patterned coating film, thereby bonding the first substrate and the second substrate.

[0095] [Coating film formation process] The method for preparing the curable composition is not particularly limited, and the composition can be prepared by various methods. The various components may be mixed and prepared just before curing, or all the components may be mixed and prepared in advance in a one-liquid state and stored at a low temperature.

[0096] In the coating film forming step, the coating film is formed by applying the prepared curable composition onto a substrate. Methods for applying the curable composition onto a substrate include spin coating, roll coating, printing, bar coating, etc. In the laminate used in the image sensor, the thickness is, for example, 0.01 μm to 200 μm, preferably 0.1 μm to 150 μm, and more preferably 5 μm to 150 μm.

[0097] Examples of the substrate include a silicon wafer, a glass substrate, a resin substrate (such as a transparent resin substrate), a ceramic substrate, a semiconductor element substrate, etc. Examples of the semiconductor element substrate include a sensor substrate (more specifically, an image sensor substrate, etc.).

[0098] [Exposure process]

[0099] The coating film is irradiated with light through a photomask to form an exposed portion made of a semi-cured curable composition and a non-exposed portion. In the exposure step, active species are generated in the exposed portion by light irradiation, and functional groups in the exposed portion are polymerized to form the exposed portion in a semi-cured state.

[0100] As a light source for photocuring, a light source that emits light with the absorption wavelength of the polymerization initiator or sensitizer used may be used, and light sources having wavelengths in the range of 200 to 450 nm, such as high pressure mercury lamps, ultra-high pressure mercury lamps, metal halide lamps, high power metal halide lamps, xenon lamps, carbon arc lamps, light emitting diodes, etc., can be used. The integrated exposure dose of the exposed area irradiated with light in the exposure step is preferably 1 mJ / cm. 2 More than 50000mJ / cm 2 More preferably, it is 1 mJ / cm or less. 2 More than 20000mJ / cm 2The following is the result.

[0101] In order to remove the solvent and improve the physical properties of the cured product, heat may be applied before or after photocuring to perform pre-baking and after-baking. The curing temperature can be set to various values, but the preferred temperature range is 60 to 400°C, and more preferably 90 to 350°C.

[0102] [Development process] In the development step, the non-exposed portion is removed from the substrate with an alkaline developer to form a patterned film, which is a coating film patterned on the substrate. The alkaline developer used in the development step may be an aqueous solution containing an alkaline component. Examples of the alkaline component contained in the alkaline developer include an alkaline organic component and an alkaline inorganic component. Examples of the alkaline organic component include tetramethylammonium hydroxide (hereinafter sometimes referred to as "TMAH") and choline. Examples of the alkaline inorganic component include potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, and lithium carbonate. From the viewpoint of increasing the contrast between the exposed portion and the non-exposed portion, the concentration of the alkaline component in the alkaline developer is preferably 25% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. The temperature of the alkaline developer may be adjusted according to the developability of the coating film. Examples of methods for contacting the alkaline developer with the non-exposed portion include an immersion method, a paddle method, and a spray method.

[0103] After the alkaline developer is brought into contact with the non-exposed area in the development step, the laminate having the substrate and the exposed area (pattern film) may be washed with water and dried. When drying the laminate, for example, the moisture on the surface of the laminate after washing with water can be removed by compressed air, natural drying, or the like.

[0104] After the development step and before the lamination step described below, the pattern film may be heated to a degree that does not reduce the adhesiveness of the pattern film. The heating temperature can be appropriately set, but is preferably 40° C. or higher and 200° C. or lower.

[0105] [Lamination process] In the lamination step, the first substrate and the second substrate are laminated via the pattern film to form a laminate.

[0106] [Heating process] In the heating step, the laminate is heated to further harden the semi-hardened pattern film, thereby bonding the first substrate and the second substrate via a hardened layer made of the hardened pattern film. In the heating step, the laminate may be heated while applying a load, for example, in the range of 0.05 MPa to 100 MPa. The heating temperature in the heating step is, for example, 60°C to 300°C. Through the above steps, a substrate laminate is obtained. EXAMPLES

[0107] Examples and comparative examples of the present invention are shown below, but the present invention is not limited to the following.

[0108] [Response rate] In the following Synthesis Examples and Comparative Synthesis Examples, the reaction rates of allyl groups and vinyl groups were measured as follows.

[0109] The measurement was performed using a 400MHz NMR device manufactured by Bruker Biospin Co., Ltd. The reaction rate of the allyl group in the synthesis was measured by diluting the reaction solution to about 1% with deuterated chloroform and adding it to an NMR tube, and was calculated from the peaks derived from unreacted allyl groups / vinyl groups and the peaks derived from reacted allyl groups / vinyl groups.

[0110] [SiH value] The SiH value was calculated by the following formula (1) by making a mixture of the compound and dibromoethane, dissolving it in deuterated chloroform, and performing NMR measurement using a 400 MHz NMR manufactured by Bruker Biospin Corporation. SiH value (mmol / g) = [integral value of peaks attributable to the SiH group of the compound] / [integral value of peaks attributable to the methyl group of dibromoethane] x 4 x [weight of dibromoethane in the mixture] / [molecular weight of dibromoethane] / [weight of compound in the mixture] (1) The calculation was carried out using

[0111] [Synthesis of modified polycyclic organosiloxane P1] A mixture of 15 g of diallyl isocyanurate, 6.43 g of diallyl monomethyl isocyanurate, and 99 g of 1,4-dioxane was mixed with 0.039 g of a xylene solution of platinum-vinylsiloxane complex (Pt-VTSC-3X, a solution containing 3% by weight of platinum, manufactured by Umicore Precious Metals Japan, Inc.) to obtain solution S1. Separately, 14.49 g of 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane and 13.36 g of 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane were dissolved in 48 g of toluene to obtain solution S2.

[0112] Then, in a nitrogen atmosphere containing 3% by volume of oxygen, solution S2 was heated to a temperature of 105° C. in a 500 mL four-neck flask, and solution S1 was added dropwise to solution S2 over 1 hour. After completion of the addition, the mixture was stirred for 1 hour while maintaining the temperature at 105° C. to obtain solution S3. The reaction rate of the alkenyl group of the compound contained in the obtained solution S3 was measured by 1H-NMR, and the reaction rate was 95% or more.

[0113] Separately, 11.09 g of 1-vinyl-3,4-epoxycyclohexane was dissolved in 22 g of toluene to obtain a solution S4.

[0114] Then, in a nitrogen atmosphere containing 3% by volume of oxygen, solution S3 was heated to a temperature of 105° C., and solution S4 was added dropwise to solution S3 over 30 minutes. After completion of the addition, the temperature was kept at 105° C. and stirred for 1 hour to obtain solution S5. The reaction rate of the alkenyl group of the compound contained in the obtained solution S5 was measured by 1H-NMR, and the reaction rate was 95% or more.

[0115] Next, after cooling the solution S5, the solvents (toluene, xylene and 1,4-dioxane) were distilled off under reduced pressure from the solution S5 to obtain a solid content. Next, isobutyl isobutyrate (hereinafter referred to as "IBIB") was added to the obtained solid content to obtain a solution SP1 (P1 concentration: 70% by weight) containing a modified polycyclic organosiloxane P1. P1 was a polysiloxane compound having multiple cationic polymerizable functional groups (specifically, alicyclic epoxy groups) and multiple alkali-soluble groups (specifically, X2 groups) in one molecule, and having a cyclic polysiloxane structure and a linear siloxane structure in the main chain. In addition, the unreacted SiH groups in P1 were 9.70% of the initial SiH groups, and the SiH value indicating the number of moles of SiH groups in 1 g was 0.52 mmol / g.

[0116] [Synthesis of modified polycyclic organosiloxane P2] 19.31 g of 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane and 6.68 g of 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane were dissolved in 48 g of toluene to obtain solution S2. Also, 8.98 g of ethylene glycol monoallyl ether and 4.68 g of 1-vinyl-3,4-epoxycyclohexane were dissolved in 24 g of toluene to obtain solution S4. Except for the preparation of S2 and S4, solution SP2 (P2 concentration: 70 wt%) containing P2 was obtained by the same synthesis method as in the above [Synthesis of modified polycyclic organosiloxane P1]. The above polysiloxane compound was a polysiloxane compound having multiple cationic polymerizable functional groups (specifically, alicyclic epoxy groups) and multiple alkali-soluble groups (specifically, X2 groups) in one molecule, and having a cyclic polysiloxane structure and a linear siloxane structure in the main chain. The amount of unreacted SiH groups in P2 was 9.70% of the initial SiH groups, and the SiH value, which indicates the number of moles of SiH groups per 1 g, was 0.57 mmol / g.

[0117] [Synthesis of modified polycyclic organosiloxane P3] 6.38 g of ethylene glycol monoallyl ether and 3.33 g of 1-vinyl-3,4-epoxycyclohexane were dissolved in 24 g of toluene to obtain solution S4. Except for the preparation of S4, the same synthesis method as in the above [Synthesis of modified polycyclic organosiloxane P1] was used to obtain solution SP3 (P3 concentration: 70 wt%) containing P3. The above polysiloxane compound had multiple cationic polymerizable functional groups (specifically, alicyclic epoxy groups) and multiple alkali-soluble groups (specifically, X2 groups) in one molecule, and was a polysiloxane compound having a cyclic polysiloxane structure and a linear siloxane structure in the main chain. In addition, the unreacted SiH group in P3 was 9.70% of the initial SiH group, and the SiH value indicating the number of moles of SiH groups in 1 g was 0.53 mmol / g.

[0118] [Synthesis of modified polycyclic organosiloxane P4] 9.66 g of 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane and 20.03 g of 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane were dissolved in 48 g of toluene to obtain solution S2. Also, 3.79 g of ethylene glycol monoallyl ether and 1.98 g of 1-vinyl-3,4-epoxycyclohexane were dissolved in 24 g of toluene to obtain solution S4. Except for the preparation of S2 and S4, the same synthesis method as in the above [Synthesis of modified polycyclic organosiloxane P1] was used to obtain solution SP4 (P4 concentration: 70 wt%) containing P4. The above polysiloxane compound was a polysiloxane compound having multiple cationic polymerizable functional groups (specifically, alicyclic epoxy groups) and multiple alkali-soluble groups (specifically, X2 groups) in one molecule, and having a cyclic polysiloxane structure and a linear siloxane structure in the main chain. Moreover, the amount of unreacted SiH groups in P4 was 9.70% of the initial SiH groups, and the SiH value, which indicates the number of moles of SiH groups per 1 g, was 0.48 mmol / g.

[0119] [Synthesis of modified polycyclic organosiloxane P5] 14.49 g of 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane and 8.37 g of 1,1,3,3,5,5-hexamethyltrisiloxane were dissolved in 48 g of toluene to obtain solution S2. Also, 6.38 g of ethylene glycol monoallyl ether and 3.33 g of 1-vinyl-3,4-epoxycyclohexane were dissolved in 24 g of toluene to obtain solution S4. Except for the preparation of S2 and S4, solution SP5 (P5 concentration: 70 wt%) containing P5 was obtained by the same synthesis method as in the above [Synthesis of modified polycyclic organosiloxane P1]. The above polysiloxane compound was a polysiloxane compound having multiple cationic polymerizable functional groups (specifically, alicyclic epoxy groups) and multiple alkali-soluble groups (specifically, X2 groups) in one molecule, and having a cyclic polysiloxane structure and a linear siloxane structure in the main chain. Furthermore, the amount of unreacted SiH groups in P5 was 9.70% relative to the initial SiH groups, and the SiH value, which indicates the number of moles of SiH groups per 1 g, was 0.58 mmol / g.

[0120] [Synthesis of modified polycyclic organosiloxane P6] A mixture of 15 g of diallyl isocyanurate, 10.72 g of diallyl monomethyl isocyanurate, and 99 g of 1,4-dioxane was mixed with 0.047 g of a xylene solution of platinum-vinyl siloxane complex (Pt-VTSC-3X, manufactured by Umicore Precious Metals Japan, a solution containing 3% by weight of platinum) to obtain solution S1. In addition, 33.06 g of 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane was dissolved in 66 g of toluene to obtain solution S2. In addition, 31.97 g of 1-vinyl-3,4-epoxycyclohexane was dissolved in 24 g of toluene to obtain solution S4. A solution SP6 containing P6 (P6 concentration: 70% by weight) was obtained by the same synthesis method as in the above [Synthesis of modified polycyclic organosiloxane P1], except for the preparation of S1, S2, and S4. The polysiloxane compound had multiple cationic polymerizable functional groups (specifically, alicyclic epoxy groups) and multiple alkali-soluble groups (specifically, X2 groups) in one molecule, and had a cyclic polysiloxane structure in the main chain. In addition, the unreacted SiH group in P6 was 9.70% of the initial SiH group, and the SiH value, which indicates the number of moles of SiH group per 1g, was 0.59mmol / g.

[0121] [Preparation of other ingredients] As materials for the curable composition, in addition to the above solutions SP1 to SP6 and IBIB, the following materials were prepared. Benzophenone-based compound as a photoradical polymerization initiator ("Omnirad (registered trademark) 651" manufactured by IGM Resins, hereinafter referred to as "Omnirad 651") 4-Hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (manufactured by Evonik, hereafter referred to as "H-TEMPO") as a radical scavenger Silane coupling agent as an adhesion promoter for glass and Si substrates ("KBM9659" manufactured by Shin-Etsu Chemical Co., Ltd., hereinafter referred to as "KBM9659") 2-Methyl-3-butyn-2-ol (MBO, manufactured by Shin-Etsu Chemical Co., Ltd.; hereafter referred to as MBO) as a platinum stabilizer Hindered phenolic compound as an antioxidant (BASF's "Irganox1010"; hereinafter referred to as "Irganox1010") Tris-(2-acryloxyethyl)isocyanurate as a photoradical crosslinking agent ("A9300" manufactured by Shin-Nakamura Chemical Co., Ltd., hereinafter referred to as "A9300")

[0122] [Preparation of Curable Composition] The materials shown in Table 1 were mixed in the amounts shown in Table 1 to obtain photosensitive compositions PS1 to PS6 used in the examples and comparative examples. When the curable compounds P1 to P6 were mixed, they were mixed as solutions SP1 to SP6, respectively. In Table 1, the amount of IBIB in the photosensitive compositions PS1 to PS6 includes the amount of IBIB in the solutions SP1 to SP6.

[0123] [Table 1]

[0124] [Preparation of simulated optical semiconductor device samples] Hereinafter, methods for producing simulated optical semiconductor devices of Examples 1 to 5 and Comparative Example 1 will be described.

[0125] [Pattern film formation] Each of the curable compositions shown in Table 1 was applied onto a glass plate as a glass substrate using a spin coater so that the thickness of the coating film after pre-baking would be 100 μm, and the coating was pre-baked by heating on a hot plate at a temperature of 85° C. for 5 minutes and then at a temperature of 120° C. for 10 minutes to obtain Sample 1.

[0126] Next, a manual exposure machine (Dainippon Kaken Co., Ltd. "MA-1300", lamp: high-pressure mercury lamp) was used to expose the sample through a photomask with a lattice-shaped line pattern, with an integrated exposure dose of 3000 mJ / cm 2 The coating film of Sample 1 was exposed to light (specifically, soft contact exposure) by irradiating the coating film with light under the above conditions.

[0127] After the exposure, Sample 1 was left for 5 minutes in an atmosphere at 25° C., and then immersed in an aqueous TMAH solution (TMAH concentration: 2.38% by mass) as an alkaline developer for 60 seconds. Sample 1 immersed in the alkaline developer was then washed with water for 30 seconds, and the moisture on the surface was removed with compressed air to obtain Sample 2 having a semi-cured patterned film in which the coating film was patterned in a lattice shape.

[0128] [Sample 3 (a ribbed substrate obtained by dividing sample 2)] Sample 3 was cut with a dicing device to obtain Sample 3 (individualized sample) (sample with a surface of 12 mm×12 mm).

[0129] [Adhesion process] Next, using a flip chip bonder (Athlete FA's "CB-505"), the ribbed substrate obtained by the above procedure was laminated with a simulated semiconductor substrate obtained by attaching a silicon wafer to a glass epoxy substrate. In detail, the simulated semiconductor substrate was set on the stage of the flip chip bonder, and the surface of the ribbed substrate on which the ribbed material was not formed was adsorbed and fixed with a collet, and the collet was moved to a position on the simulated semiconductor substrate while checking with a camera attached to the flip chip bonder. After that, the substrates were laminated under the conditions of a collet temperature of 90°C, a stage temperature of 90°C, and a load of 4N for 30 seconds, to obtain Sample 4 in which the ribbed substrate and the simulated semiconductor substrate were laminated.

[0130] Next, the laminate of Sample 4 was heated in an oven at a temperature of 200°C for 2 hours. This caused the rib material and the semiconductor substrate laminate to adhere to each other. Next, the periphery of the rib material of the laminate of Sample 4 after heating was sealed with black sealing resin manufactured by Henkel, and heated in an oven at 165°C for 2 hours to obtain Sample 5. After heating, Sample 5 was heated at 240°C for 5 minutes and at 260°C for 15 minutes to produce a simulated sample of an optical semiconductor device having a hollow structure.

[0131] [evaluation] The evaluation methods and results of the patterning properties and reliability of Examples 1 to 5 and Comparative Example 1 will be described below.

[0132] [Patterning property evaluation test] The pattern shape of Sample 2 was observed using a 3D measuring laser microscope (LEXT OLS4000, manufactured by Olympus Corporation) and evaluated according to the following criteria. ⊚: No residue was found in the lines and spaces spaced at 50 μm intervals. ◯: Residues were generated in the lines and spaces spaced at 50 μm intervals, but not in the lines and spaces spaced at 100 μm intervals. ×: Other than ◎ and 〇 The results are shown in Table 2 below.

[0133] [Reliability through thermal shock testing] Two simulated optical semiconductor device samples were prepared for each Example and Comparative Example, and a thermal shock test was performed using a heat shock tester ("ES-57L" manufactured by Hitachi Global Life Solutions, Inc.). The thermal shock test was performed by holding the optical semiconductor device in an atmosphere of -50°C for 30 minutes, and then holding it in an atmosphere of 125°C for 30 minutes, which constituted one cycle. The simulated samples were taken out after 100 cycles, 300 cycles, and 500 cycles, and observed from the glass substrate side with an optical microscope, and the cracks and peeling of the resin were evaluated according to the following criteria.

[0134] [Delamination evaluation criteria in thermal shock tests] ⊚: No peeling of the rib material was observed in either of the two simulated samples. ○: Peeling of the rib material (more specifically, partial peeling) was confirmed in one of the two simulated samples, but the number of peeled areas (total of peeled areas on the two simulated samples) was one. ×: Peeling (more specifically, partial peeling) of the rib material was confirmed in at least one of the two simulated samples, and the number of peeled portions (total number of peeled portions in the two simulated samples) was two or more.

[0135] [Crack evaluation criteria in thermal shock tests] ⊚: No cracks were found in the rib material in either of the two simulated samples. ○: Cracks (more specifically, partial cracks) were found in the rib material of one of the two simulated samples, but the number of cracks (total of cracks in the two simulated samples) was one. ×: Cracks (more specifically, partial cracks) were found in the rib material in at least one of the two simulated samples, and the number of cracks (total number of cracks in the two simulated samples) was two or more.

[0136] The results of the thermal shock test are shown in Table 2 below. In Table 2, α is the molar amount (mol) of the cyclic siloxane compound used in synthesizing the curable composition, and β is the molar amount (mol) of the linear siloxane compound used in synthesizing the curable composition.

[0137] [Table 2]

[0138] In Comparative Example 1, an error occurred at 300 cycles, but improvements in both peeling and cracking were observed in Example 1. This is thought to be because the toughness of the resin was improved by introducing a linear siloxane structure into the main chain of the curable compound.

[0139] On the other hand, 1-vinyl-3,4-epoxycyclohexane used as a capping material for SiH groups has a hydrophobic epoxy group, and therefore residues were observed in Comparative Example 1 and Example 1. In Examples 2 to 5, when part of the 1-vinyl-3,4-epoxycyclohexane was replaced with ethylene glycol monoallyl ether having a hydrophilic hydroxyl group, the solubility in an alkaline aqueous solution increased and no residues were observed.

[0140] The above results show that the present invention can provide an optical semiconductor device with improved reliability as evaluated by thermal shock tests.

Claims

1. A curable composition comprising a modified polycyclic organosiloxane compound which is a hydrosilylation reaction product of the following compounds (α) to (δ), and in which, when the amount of substance (α) is α moles and the amount of substance (β) is β moles, the relationship 0.25≦β / α≦1.5 is satisfied: (α) a cyclic siloxane compound having at least two SiH groups in one molecule, (β) a linear siloxane compound having SiH groups at both ends, (γ) at least one selected from the group consisting of an alkenyl compound having a structure represented by the following formula (X1) and / or an alkenyl compound having a phenolic hydroxyl group: (δ) An alkenyl compound having a polymerizable functional group in one molecule. 【Chemistry 1】

2. 2. The curable composition according to claim 1, which has at least two polymerizable functional groups.

3. 2. The curable composition according to claim 1, wherein the linear siloxane compound used in the reaction is 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane.

4. The curable composition according to claim 1, which is further a reaction product with an alkenyl compound having an alcoholic hydroxyl group.

5. The curable composition according to claim 1, wherein the modified polycyclic organosiloxane compound has a SiH value of 1.20 mmol / g or less.

6. The curable composition according to claim 1 , comprising a compound containing two or more (meth)acryloyl groups.

7. The curable composition of claim 1 comprising a polymerization initiator.

8. An alkali developable resist using the curable composition according to any one of claims 1 to 7.

9. A cured product obtained by curing the curable composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Substrate laminate and image sensor using the same

    JP2019062048A